2016
DOI: 10.1016/j.scitotenv.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Phototrophic periphyton techniques combine phosphorous removal and recovery for sustainable salt-soil zone

Abstract: • Phototrophic periphyton is effective in removing P (P o and P i ) from wastewaters.• Adsorption with physiochemical characteristic dominated P removal mechanism by periphyton.• The P within periphyton is mainly in forms of Labile-P and Ca-P.• The periphyton has vast potential application in recovering P for salt-soil zone The P (P i as KH 2 PO 4 and P o as ATP) removal processes by phototrophic periphyton were investigated by determining the removal kinetics, metal content (Ca, Mg, Al, Fe, Cu, and Zn) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Between pH 8 and 9, P i accumulation increased 4-6 times, with no significant differences between treatments. These results not only demonstrated that assimilation was a minor mechanism for P i accumulation by periphyton in our 24-h experiments, but it also inferred that the addition of Ca(II) and increasing pH induced by photosynthesis promoted P i removal by Ca-phosphate precipitation or co-precipitation with carbonates at pH N 8 (Dodds, 2003;Lu et al, 2016b;Scinto and Reddy, 2003). On the contrary, b 0.1 mg/g of P i release was observed when periphyton was incubated without P i addition in the dark condition (Fig.…”
Section: Effect Of Ca(ii) On P I Accumulationsupporting
confidence: 64%
See 2 more Smart Citations
“…Between pH 8 and 9, P i accumulation increased 4-6 times, with no significant differences between treatments. These results not only demonstrated that assimilation was a minor mechanism for P i accumulation by periphyton in our 24-h experiments, but it also inferred that the addition of Ca(II) and increasing pH induced by photosynthesis promoted P i removal by Ca-phosphate precipitation or co-precipitation with carbonates at pH N 8 (Dodds, 2003;Lu et al, 2016b;Scinto and Reddy, 2003). On the contrary, b 0.1 mg/g of P i release was observed when periphyton was incubated without P i addition in the dark condition (Fig.…”
Section: Effect Of Ca(ii) On P I Accumulationsupporting
confidence: 64%
“…Therefore, periphyton could accumulate P i through bio-sorption, including assimilation, entrapment, and adsorption as mentioned above, even when no Ca(II) was added ( Fig. 2A) (Liu et al, 2016a(Liu et al, , 2016bDodds, 2003;Lu et al 2014Lu et al , 2016b. Photosynthetic-driven changes in pH are likely the driver for P i uptake under light conditions.…”
Section: Effect Of Ca(ii) On P I Accumulationmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar to the inorganic form, organic phosphorus can combine with functional groups of EPS, get adsorbed onto the attached microalgae-bacteria biomass and then be further transformed (Lu et al, 2016a). Overall, the diversified phosphorus removal pathways of attached microalgae-bacteria consortium make them attractive as a platform for an advanced phosphorus removal from surface water.…”
Section: Phosphorus Removal Pathwaysmentioning
confidence: 99%
“…In recent years, there is growing research interests in utilizing natural periphytic biofilms in wastewater treatment, nonpoint source pollution control, and remediation of polluted waters (Furey et al, 2016;Wu et al, 2014). Biotechnologies such as algae turf scrubber (ATS), rotating algal biofilm reactor (RABR), and spiral periphyton bioreactor (SPB) have been developed based on periphytic biofilms for the treatment of a variety of contaminants and have showed promising results (Christenson and Sims, 2012;Mulbry et al, 2008;Shangguan et al, 2015;Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%